Determine the Frequency of Factors Leading to Hepatic Encephalopathy in Patients with Liver Cirrhosis - Maham Abdaal, Numan Ghafoor, Zafeer-ul-Hassan Iqbal, Muhammad Usman, Saqib Hussain, Mehi Naqvi (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of factors leading to hepatic encephalopathy in patients with liver cirrhosis. Study design: Retrospective study Place and duration of study: Department of Internal Medicine, Rawalpindi Medical Universityfrom 01-07-2021 to 30-06-2022 Methodology: One hundred patients were included and divided into two groups. One group was those which developed hepatic encephalopathy while the other group was of those which did not develop any hepatic encephalopathy. Various risk factors and their frequencies were measured through a modelled hepatic encephalopathy pharmacological, clinical as well as demographic data. Comparison on the frequency of the variable seen in hepatic encephalopathy patients with non-hepatic encephalopathy was conducted for better assessment of the frequency of risk factors. Results: Seventy patients did not develop hepatic encephalopathy while 30 patients did develop hepatic encephalopathy. Fifteen patients had developed alcoholic liver cirrhosis followed by hepatitis C and non-alcoholic cirrhosis. Age greater than 60 years had a percentage of 60% within cases of hepatic encephalopathy only. Prevalence of hepatitis C cirrhosis in 36.6%, diabetes in 49%, cardiovascular disease in 51%, hepatocellular carcinoma in 6.6%, use of proton pump inhibitor in 63.3% were presented and were higher than who did not develop hepatic encephalopathy. Benzodiazepines, gamma aminobutyric acid [GABA]ergics, opioids and proton pump inhibitors each of them was associated with increased chances of hepatic encephalopathy. Conclusion: Hepatic encephalopathy was more commonly observed in older patients (60%) and more specifically in male population. Higher frequency of comorbidities (hypertension, diabetes, cardiovascular disease, ascites, alcoholic cirrhosis), CCI score and pharmacological drugs were identifiable risk factors for hepatic encephalopathy. Key words: Neurotoxicity; Cirrhosis, Complications, Hepatitis C, Deteriorate